2014
DOI: 10.1016/j.adengl.2013.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Human Papillomavirus in Nonmelanoma Skin Cancer Lesions and Healthy Perilesional Skin in Kidney Transplant Recipients and Immunocompetent Patients

Abstract: We found a wide range of HPV types (mostly HPV-β) in the skin of kidney transplant recipients and immunocompetent patients with skin cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 30 publications
1
14
0
1
Order By: Relevance
“…Test for overall effect Z = 5.12 (p < 0.00001) Three [21,23,45], four [21,23,45,49], three [21,23,45], two [21,23], and six studies [8,9,13,29,42,46] reported the prevalence of HPV 49 (β3), HPV 76 (β3), HPV 92 (β4), HPV 96 (β5), and HPV (unlisted type) in the BCC patients. Four [5,21,22,48], five [23,28,45,49,50], seven [2,21,23,28,45,47,50], two [2,21], six [2,21,23,28,45,50], five [21,23,28,45,50], four [21,23,45,…”
Section: Epidermodysplasia Verruciformis-hpv (Ev-hpv)mentioning
confidence: 99%
See 3 more Smart Citations
“…Test for overall effect Z = 5.12 (p < 0.00001) Three [21,23,45], four [21,23,45,49], three [21,23,45], two [21,23], and six studies [8,9,13,29,42,46] reported the prevalence of HPV 49 (β3), HPV 76 (β3), HPV 92 (β4), HPV 96 (β5), and HPV (unlisted type) in the BCC patients. Four [5,21,22,48], five [23,28,45,49,50], seven [2,21,23,28,45,47,50], two [2,21], six [2,21,23,28,45,50], five [21,23,28,45,50], four [21,23,45,…”
Section: Epidermodysplasia Verruciformis-hpv (Ev-hpv)mentioning
confidence: 99%
“…Out of 45 studies reported during 1991 to 2017; two studies were reported in Australia [12,13], one Romania [14], ten USA [15,16,17,18,19,20,21,22,23,24], one Argentina [1], four Netherlands [25,26,27,28], two Spain [8,11], one Brazil [29], one China [30], one UK [31], one Croatia [2], four Iran [9,32,33,34], one North Africa/France [35], one Germany/USA [36], two Greece [37,38], one Sweden/Austria [39], two Germany [40,41], five Italy [5,42,43,44,45], one Russia [46], one Germany/Poland [47], one Norway/Sweden [48] and two Sweden [49,50] (Table I). Fifteen studies were case-control and 30 studies were cross-sectional studies.…”
Section: Characteristics Of Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The most common malignancy observed in solid organ transplant recipients is non-melanoma skin cancer (NMSC) [10][11][12] and particularly in squamous cell carcinoma (relative risk 14-82) [13,14]. Many etiologic factors such as ultraviolet radiation, human papillomavirus infection, genetics and immunosuppressive therapy play an important role in the occurrence of post-transplant NMSC [15,16]. The International Society of Heart and Lung Transplantation (ISHLT) recently reported that among solid tumours, lung carcinoma is the second most common malignancy after skin carcinoma [17].…”
Section: Introductionmentioning
confidence: 99%